Изучение морфометрических параметров плодов видов рода Berberis L., интродуцированных в Донбассе - Меженский, В.Н. (Промышленная ботаника, 2006)
The article provides a study of morphometric parameters of 13 species of the genus Berberis L. from the Artemovsk Nursery Experimental Station collection. It is determined that the species features are characterized by normal variation level. The specimens of B. iliensis have large amplitude of characters variation. The plants with fruit weight of more 0.5 g are selected.